A Nonsense Mutation in COL4A4 Gene Causing Isolated Hematuria in Either Heterozygous or Homozygous State - Yang, Cheng; Song, Yuan; Chen, Zhaowei; Yuan, Xiaohan; Chen, Xinhua; Ding, Guohua; Guan, Yang; McGrath, Mary; Song, Chunhua; Tong, Yongqing; Wang, Huiming (Frontiers in Genetics, 2019)
Alport syndrome (AS) is a hereditary nephropathy characterized by glomerular basement membrane lesions. AS shows a relatively rare entity with autosomal dominant gene mutation (accounts for less than 5 percent of AS cases) and is widely believed to be a consequence of heterozygous variants in the COL4A3 and COL4A4 genes. Until now, there have been no reports of homozygous variants in genes in AS patients, and it is scarce to detect both homozygous and heterozygous variants in a single Alport syndrome pedigree. We performed genetic analysis by exome sequencing (exome-seq) in a Chinese family with AS and found four individuals harboring the COL4A4 c.4599T>G variant, a novel COL4A4 nonsense mutation which gains stop codon and results in a truncated protein. The proband and her two siblings were determined to be heterozygous, whereas their mother was homozygous. The proband satisfied the criteria for the diagnosis of AS, which included clinical manifestations of microscopic hematuria and proteinuria, and pathological features of the glomerular basement membrane (GBM), including irregular thickening and splitting. However, the other three individuals who were homozygous or heterozygous for the variant exhibited mild clinical features with isolated microscopic hematuria. In summary, we identified a novel pathogenic variant in either the heterozygous or homozygous states of the COL4A4 gene in a Chinese family with AS. Our results also suggest the severity of clinical manifestations may not be entirely attributed to by the COL4A4 genetic variant itself in patients.